The Role of Branding on Customer Loyalty in the Pharmaceutical Retail Sector of Zimbabwe: A Case Study of Pharmacies in Marondera - Munyoro, Gerald; Mapfunde, Santana Mitchell; Madzinga-Kusena, Priscilla (British Journal of Healthcare and Medical Research, 2023)
The global private retail pharmacy market is estimated to be generating over $683 billion in revenue with $280 billion of that in markets outside Europe, Japan and the United States (World Bank, 2020). Thus, the retail pharmacy sector in the modern world is the most important sector in the world and hence, the world’s biggest economies are making use of the retail pharmacy sector as an important instrument for growth (Munyoro and Dewhurst, 2010; Hameli, 2018). Thus, the shows that retail pharmacies also known as community pharmacies are playing an important role in healthcare delivery (Schumacher, 2016). In fact, these health care institutions are providing health services such as provision of drug information, medication review, treatment of minor ailments, clinical interventions, health screening, counselling on lifestyle changes, provision of both non-pharmacological and pharmacological treatments plus documentation and prevention of drug interactions or adverse drug interactions to the public (Okai et al, 2019). Hence, retail pharmacies in some economies are widely spread in many communities, with elongated trading hours and serving walk in customers without prior booking of an appointment (Wiedenmayer et al, 2006; Brooks et al, 2008). Thus, making them more reachable compared to other health care facilities and in the process immensely contributing to the health care delivery system of the world (Wiedenmayer et al, 2006). As a result, without doubt this then makes the retail pharmacy sector the most important sector in the world including Zimbabwe. According to a report by Mordor Intelligence, the Zimbabwe pharmaceutical market was valued at USD 542.4 million in 2020 and was expected to grow at a compound annual growth rate of 9.2 percent from 2021 to 2026 (www.mordorintelligence.com).